Value-Informed Communication dalam Kampanye Organisasi Nirlaba: Studi Kasus Yayasan Potads di Indonesia - Soja Anggraini, Tridias (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
Nonprofit organizational communication functions not merely as a means of information dissemination, but as an ethical practice that constructs meaning, values, and social relationships with the public. This article examines the implementation of value-informed communication in nonprofit campaigns through a case study of the Persatuan Orang Tua Anak dengan Down Syndrome (POTADS) Foundation in Indonesia. Employing a qualitative case study approach, data were collected from organizational documents, social media campaign content, and documentation of public activities. The theoretical framework integrates value-informed communication, participatory communication, legitimacy theory, and organizational identity. The findings indicate that POTADS consistently embeds values of social inclusion, equality, empathy, and empowerment into its communication messages, symbols, and participatory practices. These values are not merely articulated symbolically but are enacted through concrete and community-engaged programs. The novelty of this study lies in positioning values as the normative foundation that informs and guides nonprofit communication practices, rather than treating values as instrumental messaging tools, particularly within disability advocacy contexts. The study demonstrates that value-based communication contributes significantly to organizational legitimacy, public trust, and sustainable social attitudinal change toward individuals with Down Syndrome.